A field guide to the birds of Hawaii and the tropical Pacific - Pratt, H. Douglas (Harold Douglas), 1944- (Princeton University Press, 1987)
This is the first field guide to the identification of the birds of the islands of the tropical Pacific, including the Hawaiian Islands, Fiji, Samoa, Tonga, southeastern Polynesia, and Micronesia. It is intended both as a reference for the expert and as an introduction to birding in the region for the novice. Small enough to be carried afield, it contains much previously unpublished information about behavior, vocalizations, ecology, and distribution. The forty-five color plates depict all plumages of all bird species that breed in the islands, as well as of those that regularly visit them and the surrounding oceans, and of most species believed to be extinct on the islands. Black-and-white figures show many of the rarer visitors.Introductory sections discuss the tropical Pacific as an environment for birds, problems of birding on islands, and bird conservation. Appendixes include maps of the island groups and a thorough bibliography.